2016
DOI: 10.1039/c5cp06443k
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the hydrogen absorption process in Pd overlayers on a Au(111) surface

Abstract: The hydrogen absorption into overlayers of Pd deposited on Au(111) has been investigated by density functional theory (DFT). Hydrogen concentrations, absorption environments, and geometrical and electronic effects have been analyzed, seeking for a better understanding of the general principles governing the process and the effect of foreign supports. The results show that the absorption is more favored than in pure Pd leading to lower absorption energies and less repulsive interactions due to the surface expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
3
7
0
Order By: Relevance
“…This effect can be also explained by the density of state (DOS) changes in Au and Pd alloy. Quaino et al showed by density functional theory (DFT) calculations for Au(111) surface on Pd, that the Fermi level of an alloy was lower in energy due to the Au:Pd bond formation [54]. We have also confirmed this prediction by DFT calculations in Fig.…”
Section: Surface Adsorption / Desorption On Au-pd Alloysupporting
confidence: 78%
“…This effect can be also explained by the density of state (DOS) changes in Au and Pd alloy. Quaino et al showed by density functional theory (DFT) calculations for Au(111) surface on Pd, that the Fermi level of an alloy was lower in energy due to the Au:Pd bond formation [54]. We have also confirmed this prediction by DFT calculations in Fig.…”
Section: Surface Adsorption / Desorption On Au-pd Alloysupporting
confidence: 78%
“…This approximation is supported by previous DFT studies. 44 The local densities of states (LDOS) projected on the dband for the various structures investigated are shown in Figure 8. The d-band shows an upward shift with a decreasing shell thickness, with a slight peak narrowing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It might also be possible to have hcp + fcc 3f sites occupied as in the Pd 4 ensemble shown in Scheme 2p, similar to the structure proposed for the adsorption of hydrogen atoms on adjacent 3-fold hollow sites. 60,61 However, the repulsion between two adjacent adsorbed CO molecules suggests that this structure would be energetically unfavorable.…”
Section: C Site Distribution As a Function Of Alloy Compositionmentioning
confidence: 99%